A novel qPCR assay for the detection of African animal trypanosomosis in trypanotolerant and trypanosusceptible cattle breeds - Silbermayr, K.; Li, F.; Soudre, A.; Muller, S.; Sölkner, Johann (Public Library of Science, 2013)
This study was conducted to (i) determine the prevalence of African Animal Trypanosomosis (AAT) in tsetse challenged areas, (ii) compare conventional with qPCR detection systems and (iii) evaluate the host genetic background and biology as risk factors. AAT prevalence studies are often confronted with low levels of parasitaemia. Hence, we designed a novel qPCR assay using primers and species specific probes amplifying the Internal Transcribed Spacer 1 (ITS1) gene. Thereby all three AAT species could be detected simultaneously. 368 individuals from three cattle types (Baoulé, Zebu and hybrids) originating from 72 farms in Burkina Faso were analysed. Farmers were interviewed and morphometric measurements of the cattle taken. A chi-squared test and a logistic regression model were calculated to detect associations with infection. In our study, the overall rate of prevalence detected with the novel qPCR assay was 11.14%. Compared to conventional PCR we identified a concordance of 91.30%. We tested 41 animals positive for trypanosome DNA, five animals showed multiple infections. Zebus were twice as often infected (21.74%) compared to Baoulé (9.70%) and hybrids (9.57%). Trypanosoma vivax is the dominant species (9.24%), as compared to T. congolense (2.44%) and T. brucei (0.82%). The chi-squared tests linking the infection events to the breeds (Zebu vs. Baoulé and Zebu vs. hybrids) were on the border of significance. No significant association with other tested parameters could be detected. We introduce a novel qPCR technique for the fast, sensitive and simultaneous detection of the three AAT species. Our results suggest that associations with breed and infection exist since Zebu cattle are more likely to be infected compared to Baoulé and hybrids. Indigenous taurine cattle breeds, like the Baoulé, therefore provide a unique and valuable genetic resource.